Sedentary behavior, physical activity and cardiorespiratory fitness on leukocyte telomere length - Edwards, Meghan K. (Health Promot Perspect, 2016)
Background: Emerging work is starting to investigate the cumulative effects of moderate-to-vigorous physical activity (MVPA), sedentary behavior and cardiorespiratory fitness on health. The objective of this study was to examine the cumulative and independent associations of MVPA, sedentary behavior and cardiorespiratory fitness on leukocyte telomere length (LTL). Methods: Data from the 1999-2002 National Health and Nutrition Examination Survey (NHANES) were used (N = 1868 adults 20+ years); analyzed in 2016. Sedentary behavior and MVPA were subjectively assessed with cardiorespiratory fitness determined from a submaximal treadmill-based test; participants were classified as above or below the median values for each of these three parameters. A blood sample was obtained from each participant to assess LTL via quantitative polymerase chain reaction, with participants grouped into LTL tertiles. Results: Participants who engaged in higher MVPA, sat less and had higher cardiorespiratory fitness had an increased odds (ranging from 85% to 105%) of being in LTL tertile 3 (vs. 1). In an extended adjusted multinomial logistic regression model, only MVPA was positively associated with LTL (odds ration [OR] = 1.37; 95% CI: 0.99-1.90; P = 0.05). Conclusion: All three behavior characteristics, but particularly MVPA, may be important in preserving LTLs.